Impact of Vitiligo on Fasting Blood Sugar and Thyroid Hormone Profile on Libyan Patients - Aseel Elhwari; Noor Rajab; Tasneem Alhasoumi; Fatema Alazabi; Mariam Elahjal (AlQalam Journal of Medical and Applied Sciences, 2024)
Vitiligo is a common acquired skin disease characterized by the development of circumscribed white patches of skin. It affects 1-2% of the general population. Autoimmunity plays a significant role in the pathophysiology of vitiligo. This study was intended to assess the prevalence and association of fasting blood sugar and thyroid function abnormalities among Vitiligo patients and healthy controls. A case-control study was carried out among thirty patients with a confirmed diagnosis of vitiligo (53.3% female and 46.7% male) who attended Tripoli Central Hospital (TCH) and Tajoura Hospital for follow-up, and a matched number of control subjects were recruited randomly. All blood samples were collected to assay for the FBS test, triiodothyronine (T3), thyroxin (T4), and thyroid-stimulating hormone (TSH). According to the recent data, the mean age of patients who were involved in this study was 34.4±16.51 years, while the mean age of onset was 20.13 ±14.19. Additionally, the data revealed that there were significant differences in FBS between vitiligo patients and healthy control groups (p-value = <0.001). Moreover, there were statistically significant differences between vitiligo patients and non-vitiligo subjects in T4 (p-value = 0.042). Furthermore, there was no significant correlation between the vitiligo phenotypes and thyroid hormone levels. P-value = 0.911 Chi-Square = 0.186. According to the results of the present study, it appears that vitiligo affects both sexes, especially women. It has also been noted that generalized vitiligo was more common, and there was no correlation between patterns of vitiligo and thyroid state. البهاق هو مرض جلدي شائع يتميز بتطور بقع بيضاء ضيقة من الجلد. يؤثر على 1-2 ٪ من عامة السكان. تلعب المناعة الذاتية دورا مهما في الفيزيولوجيا المرضية للبهاق. تهدف هذه الدراسة إلى تقييم مستوى سكر الدم الصائم واضطرابات وظائف الغدة الدرقية بين مرضى البهاق و الاصحاء. أجريت على حوالي ثلاثين مريضا تم تشخيص إصابتهم بالبهاق (53.3٪ إناث و 46.7٪ ذكور) حضروا إلى مستشفى طرابلس المركزي (TCH) ومستشفى تاجوراء للمتابعة ، وشملت الدراسة عدد مماثل من الأشخاص الاصحاء تم اختيارهم بشكل عشوائي. تم جمع جميع عينات الدم للفحص لاختبار FBS ، ثلاثي يودوثيرونين (T3) ، هرمون الغدة الدرقية (T4) ، والهرمون المحفز للغدة الدرقية (TSH). وفقا للبيانات المتحصل عليها من الدراسة ، كان متوسط عمر المرضى الذين شاركوا في هذه الدراسة 34.4±16.51 سنة ، بينما كان متوسط عمر بداية ظهور المرض 20.13 ±14.19. بالإضافة إلى ذلك ، كشفت البيانات أن هناك اختلافات كبيرة في FBS بين مرضى البهاق والاصحاء بقيمة احتمالية (p value = <0.001). علاوة على ذلك ، كانت هناك فروق ذات دلالة إحصائية بين مرضى البهاق والأشخاص غير المصابين بالبهاق في T4 (p value = 0.042). علاوة على ذلك ، لم يكن هناك ارتباط كبير بين الأنماط الظاهرية للبهاق ومستويات هرمون الغدة الدرقية ( P value = 0.911 مربع كاي = 0.186(. وفقا لنتائج الدراسة الحالية ، يبدو أن البهاق يؤثر على كلا الجنسين ، وخاصة النساء. وقد لوحظ أيضا أن البهاق المعمم كان أكثر شيوعا ، ولم يكن هناك ارتباط بين أنماط البهاق وقصور الغدة الدرقية